EXPERIMENTAL HYBRID SOLAR CONCENTRATOR UNIT SYSTEM FOR SANITARY WATER - Vitali, A.; Modai, E.; Jiménez Placer, G.; Moron, I.; Zambrano, Daniel (European Scientific Journal, ESJ, 2014)
The availability of solar energy and its use for heating sanitary water is a resource that has been used since ancient times. However, current technologies allow optimization and its widespread use. In the project carried out by the National University of General Sarmiento (UNGS), it has designed an experimental system hybrid solar concentrator unit for heating water for sanitary use. This project was intended as a complement to traditional water heating for domestic use , based on a parabolic concentrator . The system was designed so that it can be used in existing conventional facilities or be installed as the primary system for heating water.All components are within the structure of the base parabolic concentrator, which allows transport and fixation. The proposed project conserves the energy consumption of a traditional water heater, develop applications and combine existing technologies in a solar tracking parabolic concentrator, so to optimize its operation. Not used the traditional flat panel, but experimented with a heat exchanger mounted in the focal zone of the concentrator. One of the main objectives of this project was to arrive at a design of an integrated product that contains all the necessary elements for operation in a single platform. This adjusted the designs and location of components achieving optimal layout of the facility, giving greater freedom in the design development and implementation of design concepts. This system will allow conventional energy saving which is normally used for purposes of domestic water heating, but plans to integrate these conventional systems. That is why we speak of a hybrid system, which uses solar energy and conventional energy (electricity or gas). Considering the average consumption that occur in a house with four people, this system can replace between 45% and 91% of the energy used for water heating use , depending on time of year and considering its application in the Argentina northwestern area. The components were sized according to the proposed operating conditions. In the case of solar energy utilization, the analysis was extended to different geographic locations of the country, analyzing performance and selecting different areas favorable for the implementation of the system. This project will lay the foundation for the future development of associated projects conducted by researchers and students of the university, such as the study of the control loops, the solar tracker system development and the possible construction of a prototype, for academic use.